Pengembangan video edukasi pencegahan otitis eksterna yang dapat diakses melalui kanal YouTube - Hamsu Kadriyan; Didit Yudhanto; Eka Arie Yuliani; Luh Ade Dita Rahayu; Abiyu Didar Haq; Haldy Dwi Febrian (Universitas Mataram, 2020)
Society on the Era of Industry revolution 4.0 as well as pandemic Covid-19, is characterized by high utilization of internet and smartphone. On the other hand, the health care personal could use this characteristic to spread the information regarding the certain disease, including otitis externa through the video that can be uploaded in YouTube canal. Otitis externa generally become the 10th most outpatient visit in the hospital; furthermore, it is important to develop the video education regarding the prevention of the disease. The video education in this report was an animation video that explain about the cause, sign and symptom, and prevention of otitis externa. The video could be accessed through YouTube canal with the address https://www.youtube.com/watch?v=4M_hUjQjs78. Society could also give a feedback on this video through google form with the address bit.ly/Otitis Eksterna in order to improve the quality of video education in the future.